Cost-effectiveness analyses of targeted therapy and immunotherapy for advanced non-small cell lung cancer in the United States: a systematic review. (4th May 2021) - Yu, Anthony; Huang, Eva; Abe, Momoka; An, Kang; Park, Sun-Kyeong; Park, Chanhyun
ABSTRACT: Introduction : Mutation-targeting and immuno-oncology drugs are revolutionizing the treatment of advanced non-small cell lung cancer (NSCLC). Cost-effectiveness analyses (CEA) of these drugs have been conducted using various analytical methods and cost-effectiveness thresholds. This systematic review provides a comprehensive summary of the available evidence. Area covered : PubMed, Embase, and Cochrane Library were used to select for CEA of targeted therapies for NSCLC in the United States published between 2008 and 2020. Among the 28 included studies, a majority were published from 2017 to 2020 ( n = 18) and more than half targeted non-squamous NSCLC ( n = 15). The most frequently evaluated therapy was pembrolizumab ( n = 11), followed by bevacizumab ( n = 8) and erlotinib ( n = 4). After 2009, all included studies applied 100, 000 or more thresholds. Thresholds of studies supported by industry (median = 150, 000) were more distributed than those of studies supported by nonprofits (median = 100, 000). Expert commentary : Medications of interest have changed and are individualized to particular mutations. The cost-effectiveness thresholds varied among sponsors but generally trended to increase over time. This review provides an overview of the available cost-effectiveness findings for stakeholders and contributes to evidence-based practice.